Analytical Review of Final Examination Questions for Fifth Grade at SDN 03 East Pontianak - Herlina, Sri; Sahrani, Sahrani; Ainin, Moh.; Nugraha, Muhamad Tisna (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This study aims to evaluate the validity, reliability, level of difficulty, differentiating power, and effectiveness of checkers on the final test of the odd semester of PABP subject in class V SDN 03 East Pontianak in the 2023/2024 academic year. Using a quantitative approach, this study analysed data using IBM SPSS Statistics 23. This study involved 30 class V students as participants. The results of the analysis of 30 multiple choice items showed that 73% were valid and 27% were invalid. From the reliability aspect, it was found that the reliability level of the items was high, namely the r coefficient of 0.899. From the aspect of difficulty level, it was found that about 13% of the items were difficult, about 73% of the items were moderate and 13% of the items were easy. From the aspect of differential power, it was found that about 39% of items were good, about 42% of items were sufficient, about 19% of items were not good. And from the aspect of eliminators, it was found that about 89% were accepted, about 8% were revised and about 3% were rejected.